Pengembangan Kompetensi Guru dalam Penerapan Model 5EIM Berbasis Teknologi di Era Digital - Angraini, Lilis Marina; Wahyuni, Reni; Lingga, Leny Julia; Wahyuni, Astri (INCOME: Indonesian Journal of Community Service and Engagement, 2025)
In the ever-evolving digital era, teachers are required to be able to integrate technology into the learning process to improve the quality of education. This community service activity aims to develop teachers’ competencies in implementing the 5EIM learning model (Engage, Explore, Explain, Elaborate, Evaluate, Integrate, and Meta-Reflect) based on technology. The methods used include training, mentoring, and classroom implementation evaluation. This activity was attended by teachers from various educational levels with diverse backgrounds in technology utilization. The results of the program showed a significant increase in teachers’ understanding and ability to design and implement the 5EIM-based learning model digitally. Furthermore, the teachers also showed a positive attitude toward the use of technology as a tool to enrich students’ learning experiences. This activity is expected to serve as a model for sustainable and adaptive professional development for teachers in response to the demands of the digital age.